Multidisciplinary outpatient rehabilitation of physical and neurological sequelae and persistent symptoms of covid-19: a prospective, observational cohort study. Issue 22 (23rd October 2022) - Albu, Sergiu; Rivas Zozaya, Nicolás; Murillo, Narda; García-Molina, Alberto; Figueroa Chacón, Cristian Andrés; Kumru, Hatice
Abstract: Purpose: This prospective, observational cohort study investigated the effects of multidisciplinary rehabilitation of post Covid-19 sequelae and persistent symptoms and their impact on patients' functioning and quality of life. Methods: From 58 patients referred for neurorehabilitation, 43 were eligible for and participated in the present study. Before and after 8 weeks of rehabilitation, patients underwent physical, neuropsychological and respiratory evaluations and assessment of functional independence, impact of fatigue and quality of life. Results: Forty of 43 individuals (52 ± 11.4 years, 24 male) completed the rehabilitation program. Fatigue (87.5%), dyspnea and/or shortness of breath (62.5%), and cognitive impairment (37.5%) were reported by both previously hospitalized and home-confined patients. Neurological sequelae (35.5%) were present only in hospitalized patients. After 8 weeks of rehabilitation, patients reported significant improvements in motor functional independence, upper and lower limb functionality, impact of fatigue on daily activities, respiratory muscle strength, cognitive performance, and quality of life. Conclusions: Post Covid-19 patients present with heterogeneous neurological, physical, and respiratory impairments requiring a multidisciplinary rehabilitation approach to reduce disability and improve functionality and quality of life. A comprehensive assessment of clinical profiles and responses to rehabilitation may facilitate the identification of rehabilitation candidates and help to design effective rehabilitation interventions. Implication for rehabilitation: Post Covid-19 patients present multiple, heterogeneous neurological, physical and respiratory impairments that are observed in both previously hospitalized and home-confined patients. Eight weeks of multidisciplinary rehabilitation may significantly reduce disability and improve functionality and quality of life. A comprehensive assessment of their clinical profile and response to rehabilitation may facilitate the identification of rehabilitation candidates and help to design more effective rehabilitation interventions.